Subpolar glaciers network as natural sensors of global warming evolution - del Carmen Dominguez, M.; Eraso, A. (Ukrainian Antarctic Journal, 2006)
Obvious increase in sea level. In the work hypotheses now in use, a third of the increase in sea level is considered to be due to water thermal dilatancy and other third would come from the melting of temperate glaciers, being unknown the origin of the last third. In the expeditions carried out both to temperate and subpolar glaciers in both hemispheres, we have observed the existence of endoglacier and subglacier flows and drainages also in subpolar glaciers. Our main work hypothesis is centred on investigating the role played by subpolar glacier discharge in global warming, as we consider this discharge may represent that unknown third of sea level increase. Response in glacier discharge is so immediate and sensitive to any variation in environment temperature that we consider that glaciers work as natural sensors of Global Warming and may offer registers of great utility as indicators to estimate its evolution. Using long time series (pluriannual) of glacier discharge we will know the temporal evolution of global warming and implementing more catchment areas in both hemispheres we will be able to know the latitude distribution of glacier discharge.